Experiences of cultural heritage digitalization in different institutions: City library in Sombor, Church library in Apatin and Sombor singing society: - Milanović Simičić, Vesna (Norma, 2023)
The goal of this work is to show the scope, possibilities and limitations of digitalization of cultural heritage in libraries, institutions or associations, which possess library-information material of homeland and significant interest for citizens and the history of the place where they are located. The research was carried out in the Sombor City Library „Karlo Bijelicki“, the Church-Native Library of the Danubian Germans in Apatin and the Sombor Singing Society. The perceived problem is how to preserve old and rare books, periodicals, records or documents in smaller communities through continuous digitization and what kind of support is necessary for that. The result of the conducted research refers to different institutions in a similar problem connected by a variety of native materials and the same goal, which is to reach as many users and funds as possible in order to start the digitization process, preserve the rich heritage and give it to the reading public in digital form. The conclusion is that it is necessary to: continuously provide funding for digitalization in all cultural institutions that have cultural and native structures, allow better compensation for employees and enable the visibility of those associations or organizations that can apply equally for digitization projects regardless of how they are administratively registered in the system. The described problems are the result of the analysis of transcripts of unstructured interviews with respondents from the mentioned institutions.